Exploiting the dynamic properties of Pt on ceria for low-temperature CO oxidation. Issue 12 (3rd June 2020) - Ferré, G.; Aouine, M.; Bosselet, F.; Burel, L.; Cadete Santos Aires, F. J.; Geantet, C.; Ntais, S.; Maurer, F.; Casapu, M.; Grunwaldt, J.-D.; Epicier, T.; Loridant, S.; et al.
Abstract : Low-temperature redispersion leads to an intermediate Pt monolayer arrangement, very active for CO oxidation. Abstract : This study explores the dynamic properties of Pt/CeO2 catalysts to develop active catalytic converters for diesel exhausts. It is now well established that single Pt atoms can be stabilised on ceria surface defects under oxidising conditions. However, their catalytic activity is rather poor. A reducing treatment is required to build more active Pt nanoparticles. A Pt/CeO2 catalyst, containing mainly atomically dispersed Pt species, was exposed to reduction steps either at 250 or 500 °C to build Pt nanoparticles. Their redispersion after oxidising treatments in oxygen at three temperatures (room temperature, 250 °C and 500 °C) as well as in a simulated diesel exhaust gas was deeply investigated using different characterisation techniques such as high angle annular dark field scanning transmission electron microscopy, in situ Raman spectroscopy, in situ X-ray diffraction, X-ray photoelectron spectroscopy and H2 -temperature-programmed reduction. The arrangement of close packed Pt clusters is a permanent event at low temperatures (<200 °C) between two pseudo-stable states of Pt on ceria: 3D hemispherical NPs under reducing conditions and isolated cations under oxidising conditions at high temperature. We have identified an intermediate 2D monolayer arrangement that coincided with low-temperature CO oxidation (TOF ≈ 4–6 × 10 −2 s −1 at 100 °C in a simulated exhaust gas containing water, NO and propene). These Pt rafts combine 100% Pt dispersion with specific electronic properties and highly reactive interfacial oxygen species.